The localization and function of p38α mitogen‐activated protein kinase in rat oocytes. (12th February 2018) - Hu, S; Yu, Q; Wang, Y; Ke, D; Zhou, F; Cheng, G; Xia, W; Zhu, C
Contents: P38α mitogen‐activated protein kinase (MAPK), which is a member of the canonical MAPK family, is activated in response to various extracellular stresses and plays a role in multiple cellular processes. In this study, we investigated the expression, subcellular localization and functional roles of p38α MAPK during the meiotic maturation of rat oocytes. We found that p38α MAPK phosphorylation (p‐p38α MAPK, indicative of p38α MAPK activation) was low at the germinal vesicle (GV) stage, increased 3 hr after germinal vesicle breakdown (GVBD) and maintained its maximum at metaphase I (MI) or metaphase II (MII). The p‐p38α MAPK mainly accumulated in the GV and had no obvious expression in the nucleus. From GVBD to MII, p‐p38α MAPK was distributed in the cytoplasm around either the chromosomes or the spindle. We used SB203580, an inhibitor of p38α MAPK, to investigate the possible functional role of p38α MAPK during rat oocyte meiotic maturation. Treatment of GV stage oocytes with 20 μM SB203580 blocked p‐p38α MAPK activity, and the spindles appeared abnormal. Additionally, the rate of GVBD after 3 hr of culture with 20 μM SB203580 (58.8%) was significantly inhibited compared with the control (82.5%, p  <   .05), and the polar body extrusion rate after 12 hr of culture with SB203580 was also significantly decreased compared with the control (40.1% vs 73.3%, p  <   .05). Taken together, these data indicate that p38α MAPK may play a vital role in rat oocyte meiotic maturation.